Influence of shear stress, organic loading rate and hydraulic retention time on the biofilm structure and on the competition between different biological aggregate morphotypes. Issue 3 (June 2022) - Pechaud, Yoan; Peyre Lavigne, Matthieu; Bessiere, Yolaine; Ochoa, Juan Carlos; Queinnec, Isabelle; Paul, Etienne
Abstract: This study aimed at understanding how growth conditions influence the biofilm structural properties and the competition between microbial aggregates (biofilms, streamers, suspended biomass). The biological aggregates were developed during more than one month with constant C/N ratio (25 gCOD/gN) but under contrasted conditions in terms of shear stress, hydraulic retention time (HRT), apparent surface organic loading rate (SOLR) (fourteen conditions). At high HRT (absence of streamers) an increase of shear stress led to a decrease of the average biofilm thickness whereas it increased with the apparent SOLR. In addition, biofilm density increased with shear stress and with the apparent SOLR at high shear stress. The presence of streamers was observed only at low HRT (< 3 h). This presence has been attributed to the residual concentration in the bulk and to the hydrodynamic conditions of growth. Turbulent conditions and low substrate concentration considerably favor the development of streamers which benefit from a higher external mass transfer compared to biofilms due to their flapping movement. In some conditions, the mass of streamers in the reactor were close to the biofilm one's, highlighting the necessity to consider such morphotypes in further studies since they can have a significant impact on the global microbial activity. Graphical Abstract: ga1 Highlights: Biofilm structure depends on shear stress ( τ p ) and organic loading rates (SOLR). The influence of SOLR on biofilm thickness and density depend on the τ p applied. An increase of τ p leads to a decrease of thickness and an increase of density. Competition between aggregate morphotypes is studied considering mass transfer and detachment. Streamers presence was attributed to the low bulk residual substrate concentration.